Marcolphus on the philosophical margraviate. A commentary on Derrida’s ‘Margins of philosophy’ - Pawliszyn, Aleksandra (Hybris, 2013)
In polemics with the author of ‘Margins of philosophy’, our attitude — in general — firstly stresses the transcendental aspects of European philosophy, in the frame of which it is stated that the human being has no power over that which is out of the possibility of his learning — and in that way borders on the human world as it is comprehended and determined by the human learning endowment. The border comprehended as the above, is not a hard entity, but rather — trembling-vibrating, as if a waving “tissue of corporeality” (M. Merleau-Ponty). Secondly, based on the model laid out by phenomenological meditative learning activity, we reveal that the topic of the margin deprives the center — just as the margin is the center of Derrida’s considerations… The poetical character of the note in the margins illustrates our presumption that philosophizing grows from the life and death world — on the breach of which sometimes a scrambling-scoffing man is attached.